Sustainable Design and Construction for Geomaterials and Geostructures : Proceedings of the 5th GeoChina International Conference 2018 – Civil Infrastructures Confronting Severe Weathers and Climate Changes : From Failure to Sustainability, held on July 23 to 25, 2018 in HangZhou, China /: Proceedings of the 5th GeoChina International Conference 2018 – Civil Infrastructures Confronting Severe Weathers and Climate Changes : From Failure to Sustainability, held on July 23 to 25, 2018 in HangZhou, China. ([2019]) - Unknown
No abstract available